2021
DOI: 10.1155/2021/9703682
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Hepatoprotections of Ganoderma lucidum Polysaccharides against Multiple Organ Dysfunction Syndrome in Mice

Abstract: Background. The liver is one of the most commonly affected organs in multiple organ dysfunction syndrome (MODS). In recent years, there have been many studies on Ganoderma lucidum polysaccharides (GLP), but the role of GLP in MODS is still unclear. The purpose of this work was to explore the antioxidant, anti-inflammatory, and protective effects of GLP on the liver in MODS model mice. Methods. The characteristic properties of GLP were processed by physicochemical analysis. The MODS models were successfully est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…The above results indicated that CGLP was successfully extracted with moderate molecular weight, which may have good biological activity (S. Y [ 36 ]. Compared with the GLPs extracted by Zhang Yiwen [ 37 ] and Zhou Dong [ 38 ], CGLP has obvious differences in monosaccharide composition and polysaccharide molecular weight, indicating that the composition of GLPs differ according to the Ganoderma lucidum species, place of origin, and extraction method [ 39 , 40 ]. The CGLP extracted in this experiment may contain new polysaccharide components and structures.…”
Section: Resultsmentioning
confidence: 99%
“…The above results indicated that CGLP was successfully extracted with moderate molecular weight, which may have good biological activity (S. Y [ 36 ]. Compared with the GLPs extracted by Zhang Yiwen [ 37 ] and Zhou Dong [ 38 ], CGLP has obvious differences in monosaccharide composition and polysaccharide molecular weight, indicating that the composition of GLPs differ according to the Ganoderma lucidum species, place of origin, and extraction method [ 39 , 40 ]. The CGLP extracted in this experiment may contain new polysaccharide components and structures.…”
Section: Resultsmentioning
confidence: 99%
“…sobolifera polysaccharides (IC 50 of 0.97 mg/mL) . Moreover, the found DPPH radical scavenging activity of the PS-MSR is higher than those of both the Ganoderma lucidum polysaccharides . The mentioned pieces of evidence suggest a great antioxidant capability of the PS-MSR sample toward antioxidant properties of rich d -fructose-containing polysaccharides, which has been explored from the roots of M.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term effects of diabetes reveal the dysfunction and failure of many organs [ 20 ]. Many experiments have shown that animals with induced diabetes have a higher level of oxidative stress and redox imbalance is closely related to disease development [ 35 ].…”
Section: Bioactivity Of Polysaccharides From Ganoderma Lucidummentioning
confidence: 99%
“…However, after applying the polysaccharide (GLPs) to a group of animals, the ultrastructure of the mitochondria of the pancreatic islet cells was maintained by restoring the redox balance [ 35 ]. Excessive production of ROS in cells damages the mitochondrial membrane, oxidizes proteins, introduces mutations into DNA, which ultimately causes mitochondrial dysfunction [ 20 , 72 ]. Most of the endogenous ROS are of mitochondrial origin and indirectly contribute to the development of insulin resistance [ 73 , 74 ].…”
Section: Bioactivity Of Polysaccharides From Ganoderma Lucidummentioning
confidence: 99%